2004
DOI: 10.1016/j.virol.2003.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of vertebrate retroviruses and envelope capture

Abstract: Retroviruses are members of the superfamily of retroelements, mobile genetic elements that transpose via an RNA intermediate. However, retroviruses are distinct from other retroelements in that their "transposition" is not confined to single cells but extends to neighboring cells and organisms. As such, the "transposition" of these elements is defined as infection. It appears that a key step in the conversion of a retrotransposon into a retrovirus is the modular acquisition or capture of an envelope glycoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 70 publications
0
51
0
1
Order By: Relevance
“…ERV lineages do not persist indefinitely in their host but rather cease replicating after a predictable time (28): Proliferation and cross species transmission might be regarded as alternate responses to lineage extinction. Among IAPs, we find no cases of cross-species transmission after loss of env, and, indeed, no cases of env capture by env-less vertebrate ERVs are known (29). However, we cannot preclude the possibility that such capture might occur.…”
Section: Discussionmentioning
confidence: 65%
“…ERV lineages do not persist indefinitely in their host but rather cease replicating after a predictable time (28): Proliferation and cross species transmission might be regarded as alternate responses to lineage extinction. Among IAPs, we find no cases of cross-species transmission after loss of env, and, indeed, no cases of env capture by env-less vertebrate ERVs are known (29). However, we cannot preclude the possibility that such capture might occur.…”
Section: Discussionmentioning
confidence: 65%
“…Notably though, alignment of the HTLV-1 SU with that of the Friend-murine leukemia virus (F-MLV) reveals highly conserved microdomains within the SU and underscores a similar general organization of the SU (Kim et al, 2000(Kim et al, , 2004a (Figure 2). Functional evaluation of different SU domains, as delineated in Figure 2, allowed us to demonstrate that, paradoxically to its 'complex' genetic organization, the HTLV SU has a modular organization that is identical to that of simple retroviruses (Battini et al, 1995), with the RBD residing at the SU amino terminal (Kim et al, 2000(Kim et al, , 2004b.…”
Section: Htlv-1: a Complex Deltaretrovirus With A Simple Gammaretrovimentioning
confidence: 97%
“…Basyuk et al (2003) have previously shown that MLV Env redirects endogenous retroviral RNA-Gag trafficking from intracellular lysosomes to exiting endosomes. Based on these observations and several phylogenetic considerations on the dichotomy between the evolutionary pattern of retroviral env genes and the remainder of the retroviral genome (Malik et al, 2000;Benit et al, 2001;Pearson and Rohrmann, 2002;Kim et al, 2004a), we have postulated that infectious gammaretroviruses emerged upon env gene 'capture' by endogenous retrotransposons (Kim et al, 2004a). Thus, it is possible that upon 'capture' of an env gene, intracellular interactions between Env and its cell receptor foster the routing of the virus out of the cell (Kim et al, 2004a).…”
Section: Htlv Receptor and Coreceptor Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the crystal structure for HTLV-1 SU has not yet been determined, rigorous examination suggests that the SU is comprised of two autonomously folding domains separated by a proline-rich linker peptide (31)(32)(33)(34)(35)(36). The N-terminal region, also known as the receptor-binding domain (RBD), is necessary and sufficient for binding to Glut-1 on target T cells (21,33).…”
mentioning
confidence: 99%